A trace metal cleaning protocol for laboratory equipment to enhance the repeatability of methanotroph cultures - Marie Noguer; Sandrine Chifflet; Sylvain Davidson; Florian Haitz; Bernard Angeletti; Jean Borgomano; Bernard Ollivier; Alain Dolla; Yannick Combet-Blanc (MethodsX)
Microbial metabolism relies on metal-dependent enzymes, making trace metal contamination in liquid cultures a critical factor in biotechnological processes. This is particularly relevant for aerobic methanotrophs such as Methylotuvimicrobium alcaliphilum 20Z, a promising bacterium for methane valorization. Despite using conventional cultivation methods (Milli-Q water, analytical-grade reagents, autoclave sterilization), cultures in instrumented bioreactors exhibited poor reproducibility in growth and metabolite production. To address this issue, we developed the “trace metal free” protocol, a specific treatment dedicated to cleaning and removing trace metal contamination from laboratory equipment in order to improve culture stability.This proposed approach may be beneficial for any microbial culture requiring precise control of trace metal exposure, thereby enhancing the repeatability and productivity of cultures. • The “trace metal free” protocol treatment combining ultrapure water with an acid wash and sonication steps was applied to remove trace metals from labware and culture vessels. • Based on a series of batch cultures, the efficiency of the “trace metal free” protocol treatment was demonstrated by the improvement in repeatability of both growth on methane and formate yield (Y formate/methane) parameters known to be closely dependent on the presence of tungsten in the culture medium. • The 2-hour treatment protocol enabled stable microbial growth from the first batch, whereas untreated cultures required four sequential batches to reach comparable stability.